Agresión física y psicológica entre las parejas de novios y enamorados en la ciudad de Machala durante el año 2012. - Espinoza Apolo, Gonzalo Sigifredo (2014)
This research work is especially based on the lack of a rule that punishes physical and psychological aggression between dating couples and lovers. We have focused our work in this sector of the population living in the city of Machala.